Cyclic fatigue resistance of novel Genius and Edgefile nickel-titanium reciprocating instruments - Carlos Roberto Emerenciano Bueno; Marina Tolomei Sandoval Cury; Ana Maria Veiga Vasques; Gustavo Sivieri-Araújo; Rogério Castilho Jacinto; João Eduardo Gomes-Filho; Luciano Tavares Angelo Cintra; Eloi Dezan-Júnior (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract: This study aimed to assess the cyclic fatigue resistance of Genius and EdgeFile X1 reciprocating instruments compared with WaveOne Gold Primary. Twenty Genius (Ultradent) 25.04, 20 Genius 30.04, 20 EdgeFile X1 (EdgeEndo) and 20 WaveOne Gold Primary (Dentsply Maillefer) instruments were included in this study and tested in a static cyclic fatigue testing device, which has an artificial stainless steel canal with a 60° angle of curvature and a 5-mm radius of curvature. All instruments were operated in reciprocation mode until fracture occurred. The number of cycles to failure (NCF) was calculated and time to fracture (TF) was recorded in seconds using a digital chronometer. The mean and standard deviations of NCF and TF were calculated for each reciprocating system and the data were subjected to Kruskal-Wallis one-way analysis of variance and to Dunn's test (p < .05) using SigmaPlot software (Systat software, CA, USA). The fractured surfaces of five instruments from each brand were randomly examined and microphotographed by a low-vacuum environmental scanning electron microscopy - SEM (Tabletop Microscope TM3030, Hitachi, Japan) to confirm the cyclic fatigue fracture. EdgeFile exhibited the highest cyclic fatigue resistance, followed by both Genius files (p < .05). Within the limitations of this in vitro study, EdgeFile X1 instruments had significantly higher cyclic fatigue resistance than did Genius and WaveOne Gold Primary instruments. The cyclic fatigue resistance of both Genius files was higher than that of WaveOne Gold Primary.